Access to Judicial Remedies for Palm Oil Workers Under Poor Working Conditions in Indonesia - Ratih Ananda Putri Goestoro (Universitas Airlangga, 2022)
Most palm oil workers in Indonesia are employed as temporary daily workers. Their situations are prone to human rights violations ranging from the right to fair working conditions to the freedom of association. Under international law, palm oil workers should have the right to remedies for these human rights violations. The third pillar of the United Nations Guiding Principles on Business and Human Rights (UNGPs) provides that remedies for victims of business-related human rights violations can be accessed through judicial or non-judicial means. Under Indonesian Law, palm oil workers working under poor conditions can access their remedy through judicial mechanisms, such as the Industrial Relations Court, Civil Court or Criminal Court. However, current Indonesian Law does not provide adequate access to remedies for palm oil workers in Indonesia because the law does not provide the obligation to provide remedies under the UNGPs. Therefore, these palm oil workers do not have adequate access to a judicial remedy. Palm oil workers in remote areas face legal, procedural, and practical barriers in obtaining remedies. This article aims to find the judicial avenues these workers could use to access remedies and overcome their challenges.